2021
DOI: 10.7717/peerj-pchem.16
|View full text |Cite
|
Sign up to set email alerts
|

High throughput virtual screening of 230 billion molecular solar heat battery candidates

Abstract: The dihydroazulene/vinylheptafulvene (DHA/VHF) thermocouple is a promising candidate for thermal heat batteries that absorb and store solar energy as chemical energy without the need for insulation. However, in order to be viable the energy storage capacity and lifetime of the high energy form (i.e., the free energy barrier to the back reaction) of the canonical parent compound must be increased significantly to be of practical use. We use semiempirical quantum chemical methods, machine learning, and density f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…In a previous study 32 we have shown that chemical space of MOST candidates can be searched efficiently by genetic algorithms and we apply a similar approach here. The chemical space shown in Figure 2 is encoded by a gene like that shown in Figure 3.…”
Section: The Genetic Algorithmmentioning
confidence: 99%
“…In a previous study 32 we have shown that chemical space of MOST candidates can be searched efficiently by genetic algorithms and we apply a similar approach here. The chemical space shown in Figure 2 is encoded by a gene like that shown in Figure 3.…”
Section: The Genetic Algorithmmentioning
confidence: 99%
“…Previous work has been done on a similar database, focusing directly on the thermochemical properties. 14 Our focus here is predicting the dipole moments and how they relate to the thermochemical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22−24 In the recent decades, with the development of low-cost quantum mechanical methods, researchers are able to simulate over-large molecular libraries by high-throughput virtual screening. 25 The low-cost quantum mechanical methods or predictive machine learning (ML) models, when coupled with a proper molecular representation and evolutionary algorithms, make extremely efficient possible optimization of a certain molecular property in any predefined chemical subspace, with minimal human interference. 26 Although there has been exciting progress in rational or inverse design of molecular electrocatalysts, due to sluggish charge transfer kinetics with the electrode, efforts have been made to immobilize molecular electrocatalysts onto an electric conducting substrate to achieve heterogenization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In terms of an atomic-level understanding of the active site and manipulatable local environment, molecular systems, especially transition metal phthalocyanines and porphins, could outperform SACs since their geometric and electronic structures are more well-defined; , hence, one can make modifications to it by substituent or through-space effects based on an understanding of the electronic structure–activity relationship to improve its property toward a certain optimum, i.e., molecular engineering. The concept has been widely applied to various energy applications including solar cells, redox flow cells, molecular photocatalysis, and homogeneous electrocatalysis. In the recent decades, with the development of low-cost quantum mechanical methods, researchers are able to simulate over-large molecular libraries by high-throughput virtual screening . The low-cost quantum mechanical methods or predictive machine learning (ML) models, when coupled with a proper molecular representation and evolutionary algorithms, make extremely efficient possible optimization of a certain molecular property in any predefined chemical subspace, with minimal human interference …”
Section: Introductionmentioning
confidence: 99%